2016
DOI: 10.1016/j.cgh.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Serum Biomarkers Indicate Long-term Reduction in Liver Fibrosis in Patients With Sustained Virological Response to Treatment for HCV Infection

Abstract: BACKGROUND & AIMS Sustained virological response (SVR) to antiviral therapy for hepatitis C virus (HCV) correlates with changes in biochemical measures of liver function. However, little is known about the long-term effects of SVR on liver fibrosis. We investigated the effects of HCV therapy on fibrosis, based on the Fibrosis-4 (FIB4) score, over a 10-year period. METHODS We collected data from participants in the Chronic Hepatitis Cohort Study—a large observational multicenter study of patients with hepatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 22 publications
0
48
0
Order By: Relevance
“…Similarly, more than 80% of patients with persistently high FIB‐4/APRI scores had a diagnosis of cirrhosis, providing support to the validity of cirrhosis definition. Few patients with a cirrhosis diagnosis had persistently low FIB‐4/APRI score—an observation that was not entirely unexpected given the relatively low sensitivity of most noninvasive markers in identifying advanced fibrosis (including FIB‐4 and APRI at the cutoffs used for this study) . We explored the possibility that this subgroup might have been misclassified as cirrhosis; however, we did not find any significant differences in the distribution of cirrhosis diagnoses codes (number of instances, types) between cirrhosis patients with low versus high FIB‐4/APRI.…”
Section: Discussionmentioning
confidence: 77%
“…Similarly, more than 80% of patients with persistently high FIB‐4/APRI scores had a diagnosis of cirrhosis, providing support to the validity of cirrhosis definition. Few patients with a cirrhosis diagnosis had persistently low FIB‐4/APRI score—an observation that was not entirely unexpected given the relatively low sensitivity of most noninvasive markers in identifying advanced fibrosis (including FIB‐4 and APRI at the cutoffs used for this study) . We explored the possibility that this subgroup might have been misclassified as cirrhosis; however, we did not find any significant differences in the distribution of cirrhosis diagnoses codes (number of instances, types) between cirrhosis patients with low versus high FIB‐4/APRI.…”
Section: Discussionmentioning
confidence: 77%
“…However, patients who continued to exhibit F3 or F4 fibrosis are still at risk for developing HCC [55,38,56]. A meta-analysis by Messori et al, which included 25 studies from different parts of the world, showed a risk reduction of 6.7% (95% CI: 5-8) in non-cirrhotic patients vs. 22% (95% CI: [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] in patients with cirrhosis [57]. Accordingly, patients with advanced fibrosis and cirrhosis should continue to undergo surveillance for HCC every six months using ultrasonography with or without alpha-fetoprotein [38,52].…”
Section: Hcc Surveillance and Management In The Patients With Svrmentioning
confidence: 99%
“…For the patient with SVR in whom resolution of the inflammatory component is expected, the specific thresholds to define the remaining fibrosis are likely to be different than pre-SVR. Fibrosis-4 index (FIB-4) and aspartate aminotransferase to platelet ratio index (APRI) levels sharply decline after SVR and remain low compared to untreated patients [23]. Indeed, serologic tests alone appear to have suboptimal performance characteristics in predicting severity of fibrosis among those with SVR [24].…”
Section: Fibrosis Assessment After Svrmentioning
confidence: 99%
“…Studies from the IFN-era showed that while HCC risk was reduced with SVR, the incidence of HCC was constant for at least 5 years afterwards (21, 48). On the other hand, studies with long term follow-up in the IFN-era also demonstrate that SVR is associated with durable improvements in laboratory markers of liver disease severity including platelet count and albumin (48) as well as FIB-4 and APRI scores (49). Improvements in these laboratory parameters as well as fibroscan-derived liver stiffness may correlate with reductions in HCC risk, although evidence to support this is still needed.…”
Section: Hcc Surveillance After Daa-induced Svrmentioning
confidence: 99%